The Influence of Work From Home and Work Spirit on Employee Performance - Putra, Putu Diah Kurnia Pramadewi; Wijaya, I Gusti Ngurah Satria; Dewi, Ni Wayan Prasasti Cahya (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
In today's business, there are many things that can affect employee performance in achieving goals within the organization, either caused by internal company factors or internal factors themselves or from the company's external environment such as government regulations and government policies, even more so today. The Covid-19 outbreak has affected all aspects of the economy directly. Today's technology and information cannot be denied a considerable influence in influencing employee performance. Employee performance plays an important role in determining the achievement of company goals. This study aims to examine the effect of work from home and employee morale on employee performance. The data used in this study is primary data derived from questionnaires distributed to employees in companies that implement work from home during the covid-19 pandemic. The analytical technique used in this research is PLS analysis (SEM). The results of this study will be able to give preference to the management about the factors that affect employee performance in business continuity.